British American Tobacco and the "insidious impact of illicit trade" in cigarettes across Africa. Issue 5 (10th July 2008) - LeGresley, E; Lee, K; Muggli, M E; Patel, P; Collin, J; Hurt, R D
Abstract : Objectives: To provide an overview of the complicity of British American Tobacco (BAT) in the illicit trade of cigarettes across the African continent in terms of rationale, supply routes and scale. Methods: Analysis of internal BAT documents and industry publications. Results: BAT has relied on illegal channels to supply markets across Africa since the 1980s. Available documents suggest smuggling has been an important component of BAT's market entry strategy in order to gain leverage in negotiating with governments for tax concessions, compete with other transnational tobacco companies, circumvent local import restrictions and unstable political and economic conditions and gain a market presence. BAT worked through distributors and local agents to exploit weak government capacity to gain substantial market share in major countries. Conclusions: Documents demonstrate that the complicity of BAT in cigarette smuggling extends to Africa, which includes many of the poorest countries in the world. This is in direct conflict with offers by the company to contribute to stronger international cooperation to tackle the illicit tobacco trade.